C-phycoerythrin from Phormidium persicinum Prevents Acute Kidney Injury by Attenuating Oxidative and Endoplasmic Reticulum Stress - Vanessa Blas-Valdivia (MDPI AG, 2021)
C-phycoerythrin (C-PE) is a phycobiliprotein that prevents oxidative stress and cell damage. The aim of this study was to evaluate whether C-PE also counteracts endoplasmic reticulum (ER) stress as a mechanism contributing to its nephroprotective activity. After C-PE was purified from Phormidium persicinum by using size exclusion chromatography, it was characterized by spectrometry and fluorometry. A mouse model of HgCl2-induced acute kidney injury (AKI) was used to assess the effect of C-PE treatment (at 25, 50, or 100 mg/kg of body weight) on oxidative stress, the redox environment, and renal damage. ER stress was examined with the same model and C-PE treatment at 100 mg/kg. C-PE diminished oxidative stress and cell damage in a dose-dependent manner by impeding the decrease in expression of nephrin and podocin normally caused by mercury intoxication. It reduced ER stress by preventing the activation of the inositol-requiring enzyme-1α (IRE1α) pathway and avoiding caspase-mediated cell death, while leaving the expression of protein kinase RNA-like ER kinase (PERK) and activating transcription factor 6α (ATF6α) pathways unmodified. Hence, C-PE exhibited a nephroprotective effect on HgCl2-induced AKI by reducing oxidative stress and ER stress.